CARBON DISCLOSURE IN INDONESIA: PROFITABILITY, FIRM SIZE, AND ENVIRONMENTAL PERFORMANCE AS A MODERATOR - Gilbert Johan Martin Sinaga (Acceleration: Multidisciplinary Research Journal, 2026)
Climate change issues have increasingly raised awareness of corporate carbon emission disclosure. Such disclosure not only reflects corporate social responsibility but also serves as a strategic tool for gaining legitimacy from society and stakeholders. This study aims to examine the effect of profitability and firm size on carbon emission disclosure, and to analyze the moderating role of environmental performance. A quantitative approach was employed using secondary data obtained from annual reports, sustainability reports, and PROPER ratings of 40 companies listed on the Indonesia Stock Exchange (IDX) that consistently participated in the PROPER program during 2018–2022. Purposive sampling was applied, resulting in 200 observation units. Data were analyzed using Partial Least Squares (PLS) with WarpPLS 7.0 software. The results show that profitability has a positive and significant effect on carbon emission disclosure, while firm size does not have a significant effect. Environmental performance significantly moderates the relationship between firm size and carbon emission disclosure, but does not moderate the relationship between profitability and disclosure. This research contributes theoretically to the environmental disclosure literature and provides practical implications for management and regulators to promote corporate environmental transparency and accountability.